REVOCATION OF VAT EXEMPTION FOR ELECTRICITY AND WATER AND ITS IMPACT ANALYSIS - Trisandi, Dicky; Nasrudin, Rus’an (DIA: Jurnal Administrasi Publik, 2023)
Covid-19 pandemic has brought an impact on global economy which turn down the ranked of Indonesia from a country with upper middle income to lower middle income. In response to this matter, the Indonesian government has been issued several policies to increase the acceleration in economic and support economic recovery in order to optimize the state revenues which can be done by revoking of VAT exemptions on electricity and water. This research aims to explore further regarding the effect of poverty and inequality which arise from this revoking policy. The analysis conducted by microsimulation model method to measure poverty and inequality based on individual/household gains or losses caused by taxes policy. Main data obtained from national socio-economic survey data which submitted by BPS. Broadly speaking, these simulation results are indicates that this policy had slightly increases poverty rate, but did not affect on inequality. Through this research it was found an alternative way to compensate with assumption that this costs are source of additional revenue obtained from this imposition of normal VAT rates on electricity and water for households, so its distribution through cash transfers could be an effective way to fixes the poverty levels and inequality.